Hubungan Antara Memori Kerja dengan Kemampuan Lisan Pada Anak Pra-Sekolah - Jumiarti; Hikmatun Sadiah; Izzatul Jannah (Jurnal Terapi Wicara, 2024)
Background: the development of speech and language of pre-school children is one of impartant tasks of preschool education. Monitoring child development in terms of speech language skills has a long term impact on their overall growth. Purpose: the aim of the study was to determine the relationship between articulation and language development in typical preschool children. Method/Result: This study was conducted on 254 children, aged three to seven years. Articulation test by imitating word levels on all final consonants of Indonesian language in the initial, middle and final position, and language tests consisting of oral language comprehension and oral ability. Childrens’s responses were recorded and then scored for each correct response. The result showed that there was a significant correlation between articulation and language development (P=<0.05) but the correlation tended to be weak (r=0.2). Conclusion: articulation skills may be just one of many other factors that will influence language skills in preschool children. Therefore further research is needed to better understand other factors involved in language development.